2016
DOI: 10.1016/j.bbadis.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring preferred amino acid mutations in cancer genes: Applications to identify potential drug targets

Abstract: Somatic mutations developed with missense, silent, insertions and deletions have varying effects on the resulting protein and are one of the important reasons for cancer development. In this study, we have systematically analysed the effect of these mutations at protein level in 41 different cancer types from COSMIC database on different perspectives: (i) Preference of residues at the mutant positions, (ii) probability of substitutions, (iii) influence of neighbouring residues in driver and passenger mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
4
33
0
Order By: Relevance
“…Thus, we predict this substitution to be the most destabilizing in both START domains. This is also in line with global analyses of the COSMIC dataset, which found that arginine-to-glutamine and arginine-to-cysteine substitutions occur with high frequency in driver mutations [42]. The serine-to-phenylalanine mutations (S1077F in DLC-1 and S1100F in DLC-2) also abolish multiple hydrogen bonds and replace a small polar side chain with a large hydrophobic side chain.…”
Section: Cosmic Missense Mutations Disrupt Tertiary-level Interactionsupporting
confidence: 84%
“…Thus, we predict this substitution to be the most destabilizing in both START domains. This is also in line with global analyses of the COSMIC dataset, which found that arginine-to-glutamine and arginine-to-cysteine substitutions occur with high frequency in driver mutations [42]. The serine-to-phenylalanine mutations (S1077F in DLC-1 and S1100F in DLC-2) also abolish multiple hydrogen bonds and replace a small polar side chain with a large hydrophobic side chain.…”
Section: Cosmic Missense Mutations Disrupt Tertiary-level Interactionsupporting
confidence: 84%
“…Identifying driver mutations in the haystack of passenger mutations is a major outstanding problem in cancer research. Several approaches to discriminate between driver and passenger mutations have been developed, based on factors such as mutation frequency [5][6][7] , gene expression 8 , protein domain analysis 9,10 , markers of positive selection 11 , network enrichment analysis 12 and recurrently amino acid change analysis [13][14][15][16] .…”
Section: Mutational Likeliness and Entropy Help To Identify Driver Mumentioning
confidence: 99%
“…Somatic mutation data were downloaded from COSMIC Cell Lines Project ( Missense mutations and frame-shift mutations were selected and mutations reported in disagreement between individual data sources were excluded. Next, missense mutations were classified into driver and passenger and driver as proposed by Anoosha et al (Anoosha et al 2016). Putative passenger mutations were excluded and the remaining mutations were kept for downstream analysis.…”
Section: Selection Of Somatic Mutationsmentioning
confidence: 99%